A longitudinal analysis of fast-food exposure on child weight outcomes: Identifying causality through school transitions. Issue 1 (14th January 2021) - Dunn, Richard A; Nayga, Rodolfo M; Thomsen, Michael R; Rouse, Heather L
Abstract: This article investigates the effect of fast-food availability on childhood weight outcomes by gender, race, and location. We use a novel identification strategy based on changes in fast-food exposure along the route between the home and school that occur as students progress through the public school system and transition to different types of schools, e.g. from elementary school to intermediate school or from intermediate school to high school. Using a longitudinal census of height and weight for public school students in Arkansas, we find no evidence that changes in fast-food exposure are associated with changes in body mass index z -score for any student subpopulation.